2016
DOI: 10.3945/ajcn.115.119321
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat intake and reproductive hormone concentrations and ovulation in regularly menstruating women

Abstract: These results indicate that total fat intake, and PUFA intake in particular, is associated with very small increases in testosterone concentrations in healthy women and that increased docosapentaenoic acid was associated with a lower risk of anovulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 45 publications
1
56
1
4
Order By: Relevance
“…In this study, although PCOS women in both SFA categories were similar in relation to hormonal and metabolic profile, women with higher SFA intake had higher testosterone levels, as described previously[31-33]. In fact, while weight loss by hypocaloric diets has been linked to decrease in androgen levels in PCOS women [34-36], no such associations have been established with SFA content.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, although PCOS women in both SFA categories were similar in relation to hormonal and metabolic profile, women with higher SFA intake had higher testosterone levels, as described previously[31-33]. In fact, while weight loss by hypocaloric diets has been linked to decrease in androgen levels in PCOS women [34-36], no such associations have been established with SFA content.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings for ω-3 fatty acids agree with those from a cohort of 259 regularly menstruating women in the BioCycle Study, in which dietary intake of docosapentaenoic acid-a fatty acid commonly found in fish-was associated with a lower risk of anovulation. In addition, higher dietary intake of total marine ω-3 polyunsaturated fats-specifically eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid-was associated with increased luteal-phase progesterone concentrations (13). To our knowledge, there are no other studies of ω-3 fatty acids and reproductive-related endpoints in women.…”
Section: Discussionmentioning
confidence: 79%
“…In a prospective cohort study of female nurses, a higher intake of trans fatty acids (TFAs) was associated with ovulatory infertility (5) and endometriosis (6). In animal studies, a higher intake of ω-3 fatty acids has been associated with improved markers of fertility (7)(8)(9), particularly in male rodents (8,9), but evidence in humans is limited (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Kwasy tłuszczowe omega-3 pochodzenia morskiego zwiększały stężenie progesteronu, z kolei kwas dokozapentaenowy, choć nie wpływał na stężenie testosteronu, był jednak kojarzony ze wzrostem stężenia progesteronu i obniżeniem ryzyka braku owulacji. Choć wyniki tych badań sugerują rolę kwasów tłuszczowych (szczególnie wielonienasyconych kwasów tłuszczowych) w syntezie androgenów, potrzeba więcej badań na potwierdzenie tej tezy [19]. Jakość i ilość węglowodanów w diecie wpływa na metabolizm glukozy, co może mieć wpływ na wrażliwość tkanek na insulinę.…”
Section: Rola Składników Odżywczychunclassified